Impressions created by color of clothing of job applicants based on interviewer's perspective - De Leon, Maria Alexandra J.; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
In first time interactions such as in job interviews, where first impressions matter, what we wear can give non-verbal cues to the person we are meeting. Attire can either hinder or help make the impression you want. Color is one of the first points of reference when using attire to garner an impression. This study looked at color and the impressions it yielded from the respondents in the context of a job interview setting, A sample size of forty participants who have and have had experience conducting job interviews were surveyed. The respondents all came from different demographic backgrounds such as age, gender, and position and were surveyed using an online Google Form. The results show that when it comes to the respondents' general association, they lean towards positive for Blue hues and color white. After the survey it was found that there was not much difference between the respondent's general color associations and color attractions.Results also show that the preferences are mostly alike when viewed on the garments of a male applicant or a female applicant. The result of this study support Hemphill's (1996) findings where the traditional perspective of viewing blue as masculine and pink as feminine is absent. The findings this study generated also support the reduction of the so-called "gender-gap". In relation to Park's (2016) findings and in reference to Aslam's (2006) Table, the results may indicate that several factors may be influencing the respondent's cultural meaning of colors. After segragating the data by demographic factors, the results showed that the ratings were independent and have a weak reliance factors.This proved the findings insignificant for this particular part of the study. However, only the data from respondent's (ages 21-30) attraction to color as worn by male applicants yielded significant data.
Submitted January 2018.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Color in clothing